THE EFFECT OF SEXUAL APPEAL ADVERTISING TO ADVERTISING EFFECTIVENESS IN MANADO - Muslim, Abdul Wahid (Universitas Sam Ratulangi, 2014)
Advertising is very crucial in marketing. They are literally everywhere in the newspapers, magazines, on TV, on billboards, in the cinema or while surfing the Internet. In marketing campaigns, many techniques and approaches to attract customers. One of those approaches is sexual appeal. Sexy advertising can attract attention, increase retention and improve advertising consumer attitudes toward advertising. Sexual appeals in the media as an advertising strategy to inform a product with the intention to take the attention of consumers. The main objective of this study is the effect of sexual appeal advertising to advertising effectiveness in Manado. Associative method is used by this study with technique analysis is multiple regression analysis. The populations of this study are all people in Manado who ever see sexual appeal advertising in media and as the sample are 100 people who live in Manado. The result of this study infer that sexual appeal advertising have impact to advertising effectiveness. This study suggests if want to use sexual appeal in advertising, must be in the right time and right place because Sexual Appeal in advertising is controversy issue. Keywords: sexual appeal, advertising effectiveness.